Head-mounted camera as a debriefing tool for surgical simulation-based training: a randomized controlled study in Senegal - Abdourahmane Ndong; Adja C. Diallo; Armaun D. Rouhi; Diago A. Dia; Sebastian Leon; Cheikhou Dieng; Mohamed L. Diao; Jacques N. Tendeng; Noel N. Williams; Mamadou Cissé; Kristoffel R. Dumon; Ibrahima Konaté (BMC Medical Education)
Abstract Introduction Video feedback, particularly with a head-mounted camera, has previously been described as a useful debriefing tool in well-funded health systems but has never been performed in a low-resource environment. The purpose of this randomized, intervention-controlled study is to evaluate the feasibility of using video feedback with a head-mounted camera during intestinal anastomosis simulation training in a low-resource setting. Methodology This study recruited 14 first-year surgery residents in Senegal, who were randomized into control and camera groups. Both groups received reading materials and video lectures before performing a manual end-to-end intestinal anastomosis using a synthetic model. The control group received oral feedback, while the camera group’s first attempt was recorded, reviewed, and discussed before the second attempt. The primary outcomes were OSATS scores and completion time. Results There were no significant demographic differences between the groups. Both groups showed significant improvement in OSATS scores from the first to the second attempt (control group: p = 0.002; camera group: p = 0.0021). The camera group demonstrated a significant reduction in completion time on the second attempt (p = 0.0038), unlike the control group (p = 0.17). Both groups reported increased confidence in performing the task (control group: p = 0.003; camera group: p = 0.0029) and had positive perceptions of the workshop’s effectiveness. Conclusion This pilot study suggests that video feedback with a head-mounted camera is feasible and effective for debriefing during intestinal anastomosis simulation training in a low-resource setting, offering a low-cost, effective way to enhance technical skills. Further research with larger sample sizes is recommended to validate these findings and explore long-term impacts on surgical proficiency.